What We Owe Iraq : War and the Ethics of Nation Building - Feldman, Noah, 1970- (Book collections on Project MUSE., 2004)
What do we owe Iraq? America is up to its neck in nation building--but the public debate, focused on getting the troops home, devotes little attention to why we are building a new Iraqi nation, what success would look like, or what principles should guide us. What We Owe Iraq sets out to shift the terms of the debate, acknowledging that we are nation building to protect ourselves while demanding that we put the interests of the people being governed--whether in Iraq, Afghanistan, Kosovo, or elsewhere--ahead of our own when we exercise power over them. Noah Feldman argues that to prevent nation.